PENGARUH JOB SATISFACTION DAN EMPLOYEE ENGAGEMENT TERHADAP TURNOVER INTENTION PADA PT. HARAPAN JAYA MULTI BISNIS - Jhana Vasabha Winarso (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2022)
The purpose of this research is to analyze the effect of job satisfaction and employee engagement on turnover intention at PT. Harapan Jaya Multi Bisnis. The method that will be used in this research is quantitative research method by using Multiple Linear Regression. The number of population that is determined is all employees at PT. Harapan Jaya Multi Business. This research will use questionnaires that will be distributed to company employees as respondents to fullfil data in this research. The technique that is used in sampling are every employee at PT. Harapan Jaya Multi Bisnis. Independent variables are job satisfaction and employee engagement, and dependent variable is turnover intention. The analysis that is used is validity test, reliability test, multiple linear regression analysis and hypothesis test that is used are partial test (t test). Data analysis is assisted by SPSS software. After its result is analyzed, it is found that when employee's job satisfaction is increased therefore will decrease the employee's turnover intention. It can be concluded that job satisfaction and employee engagement have effect on turnover intention at PT. Harapan Jaya Multi Bisnis.